2020
DOI: 10.3390/jmse8110909
|View full text |Cite
|
Sign up to set email alerts
|

Epibenthic Harmful Marine Dinoflagellates from Fuerteventura (Canary Islands), with Special Reference to the Ciguatoxin-Producing Gambierdiscus

Abstract: The relationship between the ciguatoxin-producer benthic dinoflagellate Gambierdiscus and other epibenthic dinoflagellates in the Canary Islands was examined in macrophyte samples obtained from two locations of Fuerteventura Island in September 2016. The genera examined included Coolia, Gambierdiscus, Ostreopsis, Prorocentrum, Scrippsiella, Sinophysis, and Vulcanodinium. Distinct assemblages among these benthic dinoflagellates and preferential macroalgal communities were observed. Vulcanodinium showed the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Phylogenetic analysis (methodology described in the Supplementary file ) based on multiple alignments (Clustal2.1) of all the available DNA sequences (n = 345) of the D8–D10 region of the large sub unit (LSU) of ribosomal RNA (rRNA) [ 9 , 11 , 14 , 15 , 25 , 26 , 40 , 43 , 44 , 89 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ] distributes the Gambierdiscus genus into five major clades (clade I–V) as seen in Figure 8 . Clade II and III exclusively contain the species G. australes (Atlantic and Pacific strains) and G. excentricus (Atlantic strains), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis (methodology described in the Supplementary file ) based on multiple alignments (Clustal2.1) of all the available DNA sequences (n = 345) of the D8–D10 region of the large sub unit (LSU) of ribosomal RNA (rRNA) [ 9 , 11 , 14 , 15 , 25 , 26 , 40 , 43 , 44 , 89 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ] distributes the Gambierdiscus genus into five major clades (clade I–V) as seen in Figure 8 . Clade II and III exclusively contain the species G. australes (Atlantic and Pacific strains) and G. excentricus (Atlantic strains), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the substrate preferences of Ostreopsis spp. are still ambiguous (Vila et al, 2001;Cohu et al, 2013;Sparrow et al, 2017;Ternon et al, 2020;Tester et al, 2020), although some studies reported larger abundances on some substrates compared to others (Vila et al, 2001(Vila et al, , 2012Mohammad-Noor et al, 2007;Widiarti, 2008;Cabrini et al, 2010;Totti et al, 2010;Accoroni et al, 2011Accoroni et al, , 2012Accoroni and Totti, 2016;Yong et al, 2018;Boisnoir et al, 2019;Bravo et al, 2020;Lee et al, 2020). Such comparisons are tricky because of the limits of cell quantification in function of the type of substrate (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate areas canopy-forming algae are lost and replaced by less complex algaedominated communities (Strain et al, 2014;Vergés et al, 2014;Bulleri et al, 2016); several studies relate major densities of Ostreopsis spp. on algal turfs (Bravo et al, 2020) and in particular on highly urbanised coasts that are usually characterized by post-regime shift algal communities (Mangialajo et al, 2008a;Widiarti et al, 2008;Cohu et al, 2013), compared to healthier habitats dominated by forest-forming brown algae (Meroni et al, 2018). In tropical areas, ciguatera fish poisoning episodes recurrently follow disturbances to coral reefs by natural and artificial events such as heat waves, hurricanes, dredging, and shipwrecks, among others, where regime shifts from coral to algae are observed (de Sylva, 1994;Jouffray et al, 2015;Rains and Parsons, 2015;Johns et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations